PENGEMBANGAN WEBSITE COMPANY PROFILE KOPERASI KARYA BERSAMA MEPI (KKBM) SEBAGAI MEDIA INFORMASI DIGITAL BERBASIS WEB - Rizky Tri Wahyudi; Imamulhakim Syahid Putra (Jurnal Riset Teknik Komputer, 2026)
The advancement of digital technology encourages organizations to have representative online information media. Koperasi Karya Bersama MEPI (KKBM) as an economic institution does not yet have an official website, so information regarding its profile, activities, and services is still conveyed manually. This study aims to develop a web-based company profile website using the Laravel framework with the Rapid Application Development (RAD) method. The research results include a website featuring profile pages, announcements, documentation, member data, as well as admin and member login systems. This website is expected to serve as a transparent, professional digital information medium that supports the digitization of the cooperative. Functional testing shows that all features work properly and meet user needs. This company profile website contributes significantly to enhancing KKBM's digital image and communication effectiveness.